Analisis Potensi Wakaf Saham di Sumatera Barat - Noor Mochamad Azis Subagio; Nurul Fauzi; Muhammad Rafi (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2022)
The purpose of this study is to analyze the potential of share waqf in West Sumatra. In analyzing the potential of share waqf, researchers will relate it to the potential possessed by the people of West Sumatera both in terms of material potential and non-material potential, such as religiosity and humanist. This study uses a survey method by distributing questionnaires to 135 samples. The target sample of this research is the Muslim community of West Sumatra. Respondent data obtained will be processed using the IBM SPSS Statistic 20 application to test the validity and reliability of the data. The results of this study indicate that share waqf has enormous potential in West Sumatra. From the material side of potential, many Muslim communities in West Sumatra are familiar with investing, save regularly, and agree that investment is very important. Likewise, from the potential non-material side of religiosity, the Muslim community of West Sumatra agrees that share waqf is in accordance with Islamic law and as an innovation in muamalah. Other potential of share waqf in West Sumatra can also be seen from the potential of the humanist non-material side that shows public concern for other human beings.